2011
DOI: 10.1614/wt-d-10-00155.1
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation, Control, and Physiology of Glyphosate-Resistant Giant Ragweed (Ambrosia trifida) in Arkansas

Abstract: Glyphosate-resistant giant ragweed in Arkansas was reported in 2005. A study was conducted to (1) confirm and characterize the glyphosate resistance in giant ragweed, (2) determine if reduced absorption or translocation is the mechanism of glyphosate resistance in giant ragweed, and (3) evaluate the efficacy of nine POST-applied soybean herbicides to control glyphosate-resistant and -susceptible giant ragweed. Based on the rate required to kill 50% of plants (LD50 values), resistant giant ragweed biotypes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 28 publications
3
45
6
Order By: Relevance
“…Glyphosate plus acifluorfen provided 35% to 65% control and was equivalent to glyphosate applied alone at L1 and L2. This is in contrast to the findings of Norsworthy et al [16] who reported 76% to 87% control of glyphosate resistant giant ragweed with acifluorfen applied at 420 g a.i ha -1 . Similarly applying fomesafen with glyphosate either as a tank mix or a premix gave only 69% control ( Table 4).…”
Section: Postemergence Herbicidescontrasting
confidence: 99%
See 2 more Smart Citations
“…Glyphosate plus acifluorfen provided 35% to 65% control and was equivalent to glyphosate applied alone at L1 and L2. This is in contrast to the findings of Norsworthy et al [16] who reported 76% to 87% control of glyphosate resistant giant ragweed with acifluorfen applied at 420 g a.i ha -1 . Similarly applying fomesafen with glyphosate either as a tank mix or a premix gave only 69% control ( Table 4).…”
Section: Postemergence Herbicidescontrasting
confidence: 99%
“…Glyphosate plus fomesafen, bentazon and thifensulfuron provided less than 65% control and were equivalent to glyphosate applied alone across all locations. This is in contrast to the findings of Norsworthy et al [16] who reported 100% control of glyphosate resistant giant ragweed with fomesafen applied alone at 263 g a.i. ha -1 or bentazon applied alone at 840 g a.i.…”
Section: Postemergence Herbicidescontrasting
confidence: 99%
See 1 more Smart Citation
“…However, for 20-cm giant ragweed, lower shoot biomass reduction (< 85%) was observed compared to the visual control at 21 DAT (Table 4). Previous researchers also reported variation in the control of different giant ragweed accessions with aciflourfen, fomesafen, and lactofen (Norsworthy et al, 2011;Tylor et al, 2002). Note.…”
Section: -----------------------% -----------------------------------mentioning
confidence: 93%
“…Several PRE and POST herbicides and their combinations have been evaluated for control of giant ragweed in soybean before commercialization of herbicide-resistant crops [25]- [27]. Prior to evolution of glyphosate-resistant giant ragweed, most no-till soybean growers were applying glyphosate before planting to control the existing population followed by an early-POST application for control of newly emerged giant ragweed plants.…”
Section: Introductionmentioning
confidence: 99%